2006
DOI: 10.1093/eurheartj/ehl193
|View full text |Cite
|
Sign up to set email alerts
|

EuroHeart Failure Survey II (EHFS II): a survey on hospitalized acute heart failure patients: description of population

Abstract: Decompensated HF is the most common clinical presentation of AHF patients. More than one-third of AHF patients do not have a previous history of HF, and new-onset HF is often caused by ACS. Preserved systolic function is found in a substantial proportion of the patients. The prevalence of valvular dysfunction is strikingly high and contributes to the clinical presentation. The EHFS II on AHF verified that the use of evidence-based HF medication was well adopted to clinical practice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

86
867
25
72

Year Published

2007
2007
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 1,128 publications
(1,050 citation statements)
references
References 24 publications
86
867
25
72
Order By: Relevance
“…Also of importance is the fact that identification of CAD patients was based not only on clinical grounds, but also on coronary angiography data available in 69% of them, but also in 43% of those with non‐CAD. This is in contrast to most existing series of APE7, 10, 23 or acute heart failure,1, 2, 3, 4, 5, 13 where angiographic data are not provided. Of interest is the documentation of significant coronary artery stenosis in 32% of non‐CAD patients who underwent cardiac catheterization, pointing to the concomitant presence of CAD in patients with the primary diagnosis of valvular heart disease.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…Also of importance is the fact that identification of CAD patients was based not only on clinical grounds, but also on coronary angiography data available in 69% of them, but also in 43% of those with non‐CAD. This is in contrast to most existing series of APE7, 10, 23 or acute heart failure,1, 2, 3, 4, 5, 13 where angiographic data are not provided. Of interest is the documentation of significant coronary artery stenosis in 32% of non‐CAD patients who underwent cardiac catheterization, pointing to the concomitant presence of CAD in patients with the primary diagnosis of valvular heart disease.…”
Section: Discussionmentioning
confidence: 90%
“…Several investigators have reported on the in‐hospital mortality in patients with acute heart failure, which is an ample concept that includes acute decompensation of chronic heart failure, cardiogenic shock with or without pulmonary edema, right ventricular failure, and APE 3, 6, 14, 19, 20, 21. In these studies, mortality has varied from 6.4% to 17.2% and they have shown advanced age,6, 14, 19, 21 severe left ventricular dysfunction,14 acute coronary syndromes,14 admission blood pressure,6, 19, 21 renal failure,6, 19, 21 need for inotropics,19 and anemia19 as principal predictors.…”
Section: Discussionmentioning
confidence: 99%
“…Acute decompensated HF (ADHF) is the most common cause of hospitalization,3 and cardiogenic shock occurs in about 4% of ADHF admissions 4. Conventional inotropes improve haemodynamics and organ perfusion and relieve symptoms, but due to short half‐lives, they are limited to selected inpatients and outpatients with continuous infusions and are pro‐ischaemic, are pro‐arrhythmic, and may be associated with increased mortality 5, 6, 7, 8, 9…”
Section: Introductionmentioning
confidence: 99%
“…Heart failure (HF) is a global public health problem affecting millions worldwide 1, 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12. In the USA, the prevalence is 5.7 million and there are 670 000 new cases per year, while there are another 15 million people living with HF in Europe 13, 14, 15.…”
Section: Introductionmentioning
confidence: 99%
“…1, 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12 These registries have either focused on in‐patient characterization and short‐term outcomes or maintained separate samples of acute HF hospitalizations and chronic HF follow‐up, limiting understanding of the transition from chronic maintenance to an acute state requiring hospitalization 24, 25. No prior detailed, longitudinal evaluations of long‐term disease progression, healthcare utilization, and health economics on a global scale have been reported.…”
Section: Introductionmentioning
confidence: 99%